Geochemical modeling of element species in selected tropical estuaries and coastal water of the Strait of Malacca - Looi, Ley Juen; Aris, Ahmad Zaharin; Ng, Tzu Shan; Md. Yusoff, Fatimah; Hashim, Zailina (Elsevier, 2015)
Estuaries and coastal waters of Strait of Malacca are of Na-Cl water type. Water samples are governed by ionic exchange process and silicate weathering. Na-Cl water types indicating the presence of seawater and halite mineral. Whereas Ca/(Ca+SO4) ratio found that 71% of the water samples indicating the occurrence of Ca depletion (Ca/(Ca+SO4)<0.5). The super-saturation of carbonate minerals (calcite and dolomite) is caused by the precipitation process that continuously exchanged Ca and Mg with Na. Based on PHREEQC speciation modeling, Al(OH)4-, Ba2+, CdCl+, Cu(OH)2, Fe(OH)3, Mn2+, PbCO30, and Zn2+ are dominant metals species present in the water samples